Amandemen Lembaga Legislatif dan Eksekutif: Prospek dan Tantangan - Isra, Saldi (Unisia, 2016)
The constitutional amendments for UUD 1945 gives a new opportunity and also challenge for all. This can be seen as "fresh blood" to the nation. Beside of this new optimism, we have to aware, that there was still an "old force" that do not agree with this change. They often use decrees and regulations to eliminate the power of this new constitutions for the sake of short term political Interests. Certainly this is a threat for the sustainability of democracy in this country. Consequently, there must be a ’legal guardianship’ that can protect and maintain this change by empowering all of power across this nation.